Raif Badawi : The Voice of Freedom : My Husband, Our Story - Ensaf Haidar and Hoffmann, Andrea Claudia (London Little, Brown, 2016)
"When Raif Badawi and Ensaf Haidar fell in love with each other as adolescents, they did so in violation of every moral precept in the strictly Islamic Kingdom of Saudi Arabia. During their clandestine love affair, the young couple had no idea that, more than a decade later, Ensaf's love for Raif would attract the attention of politicians from around the world as she mobilizes global public opinion in an effort to save her husband from death at the hands of the Saudi judiciary. With a courage born of desperation, she is fighting from exile in Canada to secure the release of the father of her three children, and is bringing great pressure to bear on the murderous regime in her native country. In RAIF BADAWI: THE VOICE OF FREEDOM, Ensaf Haidar tells Raif's and her own story: the story of their love, their shared liberal ideas, and her fight to save him"--
Keywords: Political prisoners -- Saudi Arabia -- Dissenters